Effectiveness of gram staining and 10% KOH in detecting STIs from anal swabs of sexual assault victims - Renatha N.H. Nainggolan; Budi Darmanta Sembiring (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Sexually Transmitted Infections (STIs) significantly impact global reproductive health. Sodomy, defined as anal intercourse often involving coercion, poses a high risk for STI transmission. Purpose: To analyze the effectiveness of Gram staining and 10% KOH examinations in detecting pathogens from anal swabs of sexual assault victims. Method: This analytical observational study used a retrospective cross-sectional design. Medical record data from 33 sodomy victims at Dr. Pirngadi Regional Hospital, Medan (2022–2024), were analyzed using total sampling. The reporting of this section adheres to the STROBE. Results: Most victims were male (57.58%), with the 11–20 year age group being most prevalent (69.70%). Gram staining identified Gram-negative diplococci in 17 individuals (51.52%), while 10% KOH detected yeast in 4 individuals (12.12%). McNemar’s analysis yielded a p-value 0.0016 indicates that Gram staining is more effective for STI detection in this context than 10% KOH. Conclusion: Gram staining is a more reliable diagnostic method for detecting STIs in anal swab samples compared to 10% KOH. The high prevalence of bacterial infections highlights the urgent need for early STI screening in sexual assault cases.